2018
DOI: 10.1097/nne.0000000000000478
|View full text |Cite
|
Sign up to set email alerts
|

Peer Training Using Cognitive Rehearsal to Promote a Culture of Safety in Health Care

Abstract: Nursing students need opportunities to prepare for real-world problems that they may encounter as they enter the profession. Incivility and bullying behaviors persist in health care. The purpose of this project was to increase students' awareness of incivility and prepare them to respond to it. Two teaching methods were compared. Results supported that interactive civility training using cognitive rehearsal provided by nursing student peers was as effective as instruction from an expert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Such a program can be incorporated into the curriculum for students from sophomore to senior year [ 41 ]. This is in accordance with nursing students’ suggestions for early education on bullying and how to cope in school education [ 42 , 43 ]. Our study showed experience sharing among peers to deal with bullying and incivility.…”
Section: Discussionsupporting
confidence: 87%
“…Such a program can be incorporated into the curriculum for students from sophomore to senior year [ 41 ]. This is in accordance with nursing students’ suggestions for early education on bullying and how to cope in school education [ 42 , 43 ]. Our study showed experience sharing among peers to deal with bullying and incivility.…”
Section: Discussionsupporting
confidence: 87%
“…Another group of researchers used CR to teach undergraduate NSs at a public university in the southeastern United States how to respond to incidents of incivility (Roberts et al, 2018). Sophomores and seniors participated in two different instructional methods: one given by a nursing incivility expert and the second delivered by previously trained senior NSs.…”
Section: Generic Wpv Training Programsmentioning
confidence: 99%
“…In order to evaluate the intervention, NSs completed two surveys: one immediately after each method of training and the second at the end of the semester. Those surveys utilized Kirkpatrick’s four-level training evaluation model: reaction, learning, behavior, and results (Kirkpatrick & Kirkpatrick, 2006; Roberts et al, 2018).…”
Section: Generic Wpv Training Programsmentioning
confidence: 99%
See 2 more Smart Citations